Combination of probiotics enhancing butyrogenesis in colonic microbiota model of patients with ulcerative colitis - Inokuma, Kentaro; Sasaki, Daisuke; Shintani, Tomoya; Inoue, Jun; Oyama, Katsuaki; Noda, Yuta; Maeda, Takayuki; Yamada, Ryouichi; Matsuki, Yasushi; Kodama, Yuzo; Kondo, Akihiko (Applied Microbiology and Biotechnology, 2025)
Administering beneficial bacteria as probiotics to restore the intestinal microbiota and its metabolic functions, such as butyrogenesis, is a promising treatment strategy in ulcerative colitis (UC). This study aimed to investigate the effect of a combination of probiotics, consisting of the lactic acid bacterium Weizmannia coagulans SANK70258 and the lactate-utilizing butyrate-producing bacteria Anaerostipes caccae or Clostridium butyricum, on the colonic environment using an in vitro colonic microbiota culture model with fecal inoculums from seven patients with UC. Co-inoculated W. coagulans and A. caccae neither inhibited each other’s growth nor significantly affected the relative abundance of other bacterial species; however, the growth of W. coagulans was significantly inhibited when co-inoculated with C. butyricum. The relative abundance of pro-inflammatory bacteria (Escherichia sp. and unclassified Enterobacteriaceae) and Bifidobacterium spp. significantly decreased in W. coagulans-C. butyricum co-inoculated cultures. Inoculation with any of the probiotics alone did not increase butyrate production, whereas co-inoculation of W. coagulans with A. caccae or C. butyricum significantly increased the butyrate levels. Overall, the results suggested that W. coagulans and lactate-utilizing butyrate-producing bacteria in combination have synergistic effects through cross-feeding and can effectively restore butyrogenesis in the colonic environment of patients with UC.